Coronary Bypass Grafting for High-Risk Patients (Literature review) - O. Gogayeva (Ukrainian Journal of Cardiovascular Surgery, 2020)
Ischemic heart disease still remains one of the leading causes) of morbidity and mortality of population of high-developed countries. Annually we notice an increase of coronary artery bypass grafting (CABG) procedures, especially for high-risk patients.Objective. To perform literature review of CABG for high-risk patients.Results. According to literature data’s we reviewed and compared risks scores used in cardiovascular surgery for determination of patients’ severity and probability of death. The basic errors of the EuroSCORE I, II scales and the possibilities of their use in minimally invasive surgery were identified. According to modern randomized clinical trials (RCTs) comparing the OPCAB (off-pump coronary artery bypass (OPCAB) and ONCAB (on-pump coronary artery bypass) techniques, there is no clear difference in complications. Despite the small percentage of high-risk patients in RCTs (18% in the CORONARY trial), many authors consider that OPCAB has a lot of advantages for high-risk patients. Better results were obtained in elderly patients with neurocognitive disorders, porcelain aorta, diabetes mellitus, kidney insufficiency and low ejection fraction of left ventricle. Kowalewski et al. studied high-risk patients and used special statistical methods to compare patients by their risk profile. They concluded that high-risk patients have linear correlation between risk profile and increase in benefits from OPCAB: all-cause mortality (P<0.01), myocardial infarction (P<0.01) and stroke (P<0.01). According to Raja, Shahzad G., total arterial revascularization with all its advantages and improvement of survival, reduction in the number of repeated revascularizations and low stroke rates can be considered as the Holy Grail in myocardial revascularization. However, larger randomized research is needed to justify this status. Followers of ONCAB technique claim that OPCAB leads to incomplete revascularization, poor quality of grafts and repeated hospitalizations and revascularization. It should be noted that high-risk patients should be operated in expert centres by the team of skilled heart surgeons, anaesthesiologists and with competent medical support of cardiologist.